A model study of aggregates composed of spherical soot monomers with an acentric carbon shell. (January 2018) - Luo, Jie; Zhang, Yongming; Zhang, Qixing
Highlights: Acentric core–shell monomers model for soot particles with coatings is proposed. Optical diversities caused by fractal structures with identical fractal parameters are analyzed. The fractal nature of different models is preserved. The way how the individual primary particles are coated is negligible. Abstract: Influences of morphology on the optical properties of soot particles have gained increasing attentions. However, studies on the effect of the way primary particles are coated on the optical properties is few. Aimed to understand how the primary particles are coated affect the optical properties of soot particles, the coated soot particle was simulated using the acentric core–shell monomers model (ACM), which was generated by randomly moving the cores of concentric core–shell monomers (CCM) model. Single scattering properties of the CCM model with identical fractal parameters were calculated 50 times at first to evaluate the optical diversities of different realizations of fractal aggregates with identical parameters. The results show that optical diversities of different realizations for fractal aggregates with identical parameters cannot be eliminated by averaging over ten random realizations. To preserve the fractal characteristics, 10 realizations of each model were generated based on the identical 10 parent fractal aggregates, and then the results were averaged over each 10 realizations, respectively. The single scattering properties of all models were calculated using the numerically exact multiple-sphere T-matrix (MSTM) method. It is found that the single scattering properties of randomly coated soot particles calculated using the ACM model are extremely close to those using CCM model and homogeneous aggregate (HA) model using Maxwell–Garnett effective medium theory. Our results are different from previous studies. The reason may be that the differences in previous studies were caused by fractal characteristics but not models. Our findings indicate that how the individual primary particles are coated has little effect on the single scattering properties of soot particles with acentric core–shell monomers. This work provides a suggestion for scattering model simplification and model selection.